2.1.4-eg-1 - h 6 = 0. (b) To nd the slope of the tangent to...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Example Consider the curve y = f ( x ) = ( x + 1) 2 which goes through the point P (2 ,f (2)) = P (2 , 9). (a) Find the slope of the secant line joining P (2 ,f (2)) and Q (2 + h,f (2 + h )), for some h 6 = 0. (b) Using your answer in (a), what is the slope of the tangent line to the curve at the point P ? Solution: (a) The slope of the secant line joining P (2 ,f (2)) and Q (2 + h,f (2 + h )) for h 6 = 0 is given by f (2 + h ) - f (2) (2 + h ) - 2 = ((2 + h ) + 1) 2 - (2 + 1) 2 h = (2 + h ) 2 + 2(2 + h ) + 1 - 9 h = 4 + 4 h + h 2 + 4 + 2 h + 1 - 9 h = h 2 + 6 h h = h + 6 where the cancellation of h from the numerator and denominator is valid since
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: h 6 = 0. (b) To nd the slope of the tangent to the curve at the point P (2 ,f (2)), we must consider the slope of the secant line PQ as the point Q approaches P . That is, as h approaches 0. But as h gets closer and closer to zero, h + 6 gets closer and closer to 6. The slope of the tangent line to the curve at the point P (2 ,f (2)) must be 6....
View Full Document

This note was uploaded on 04/02/2012 for the course MTH 132 taught by Professor Kihyunhyun during the Fall '10 term at Michigan State University.

Ask a homework question - tutors are online